ВІКТОР МАТЮК – КОМПОЗИТОР, ПЕДАГОГ, МУЗИЧНИЙ КРИТИК, ВИДАВЕЦЬ - Стадницька Марія (International Journal of Innovative Technologies in Social Science, 2020)
The main vectors of activity of the Ukrainian priest and composer of the second half of the 19th century are revealed in the article. Victor Matyuk — one of the most consistent heirs to the traditions of the Peremyshl school in Halychyna. V. Matyuk, along with M. Verbytsky, I. Lavrivsky, I. Vorobkevych, P. Bazhansky, O. Nyzhankivsky, O. Kyshakevych and others, he belongs to elite of Ukrainian public and educational figures of Halychyna,who had received a religious education. Subsequently, life-long priesthood duties were combined with active work in many areas of social and cultural life. Based on historiographic and documentary materials, the author analyzes the stages of the artist's creative journey, the defining features of his musical thinking, the facts of pedagogical and editorial-publishing activity, the directions of music-critical and organizational activity. Much attention was paid to the characterization of V. Matyuk's personality, which emerges from the memoirs of his contemporaries and villagers, and also summarizes information about the composer's active contacts with prominent figures of Ukrainian culture of that time.